Subfemtosecond steering of hydrocarbon deprotonation through superposition of vibrational modes - Alnaser, Ali Sami; Kübel, M.; Siemering, R.; Bergues, Boris; Kling, Nora G.; Betsch, K. J.; Deng, Y.; Schmidt, J.; Alahmed, Z. A.; Azzeer, A. M.; Ullrich, J.; Ben-Itzhak, I.; et al. (Nature Communications, 2014)
Subfemtosecond control of the breaking and making of chemical bonds in polyatomic molecules is poised to open new pathways for the laser-driven synthesis of chemical products. The break-up of the C-H bond in hydrocarbons is an ubiquitous process during laser-induced dissociation. While the yield of the deprotonation of hydrocarbons has been successfully manipulated in recent studies, full control of the reaction would also require a directional control (that is, which C-H bond is broken). Here, we demonstrate steering of deprotonation from symmetric acetylene molecules on subfemtosecond timescales before the break-up of the molecular dication. On the basis of quantum mechanical calculations, the experimental results are interpreted in terms of a novel subfemtosecond control mechanism involving non-resonant excitation and superposition of vibrational degrees of freedom. This mechanism permits control over the directionality of chemical reactions via vibrational excitation on timescales defined by the subcycle evolution of the laser waveform.